Porcupine, Picayune, & Post how newspapers get their names - Bernhard, Jim (University of Missouri Press, 2007)
"Porcupine, Picayune, & Post examines the history and etymology of newspapers' names. Bernhard focuses on printed general-interest English-language dailies and weeklies, from the Choteau (Montana) Acantha to the Moab (Utah) Zephyr, with everything in between"--Provided by publisher.